1962
DOI: 10.1039/df9623400127
|View full text |Cite
|
Sign up to set email alerts
|

Rotational isomerism about single bonds in olefinic compounds

Abstract: Analysis of the 60 Mc/sec high resolution proton n.m.r. spectra of samples of allyl chloride, allyl bromide, allyl iodide and allyl benzene both neat and in 10 % (viv) solution in CC14 yield sets of coupling constants and chemical shifts from which conclusions may be drawn concerning the relative stabilities of the rotational conformers. In allyl chloride and ally1 benzene that conformer with the substituent gauche to the proton on trigonai carbon is slightly preferred. The preference for this conformer become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1964
1964
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…t Due to j v (cis) and j~v (trans) increasing in the 3-halopropenes in going from I to CI it has been remarked [8] that the chloromethyl appears to have a lower electronegativity than the iodomethyl group. $ Solvent effects [9] or differences in experimental and analytical methods may be important.…”
Section: Cu 3mentioning
confidence: 95%
“…t Due to j v (cis) and j~v (trans) increasing in the 3-halopropenes in going from I to CI it has been remarked [8] that the chloromethyl appears to have a lower electronegativity than the iodomethyl group. $ Solvent effects [9] or differences in experimental and analytical methods may be important.…”
Section: Cu 3mentioning
confidence: 95%
“…(1) where JHX is the observed coupling constant, is the fractional population in form Ia, Jhx1 and JHxg are the (H,X) coupling constants characteristic of form Ia and lb (or lb'), respectively. Solving for pa, and substituting in AF = -RTIn Keq = -RTIn 2pj(lpf) (2) one obtains AF = -RT In 2(JHx -Jnxs)l(Jnxt ~Jhx) (3) Similarly AF = -RT In (Jhy1 + JHYg ~2JHy)/(JhY -JHYg) (4)…”
mentioning
confidence: 99%
“…From all these curves, it is clear that for all halides, the c/s form is energetically more favourable than the gauche form. But the high resolution proton NMR spectral studies (Bothner-by and Gunther 1962;Govi11966) show that in 3CIP itself, there is some preference for the gauche form rather than the cis form and this tendency is much pronounced in the case of 3BrP and 3IP. This fact has been confirmed quite recently from electron diffraction study in the gas phase on 3BrP (Schei and Shen 1982) wherein it is reported that the population of the gauche form is as high as 95 %.…”
Section: Computations Results and Discussionmentioning
confidence: 99%